Current insights into monitoring of congenital adrenal hyperplasia - Leusink, Quinty M.; Verploegen, Elke E. W.; Adriaansen, Bas P. H.; Chin, Xinyi; Stikkelbroeck, Nike M. M. L.; Span, Paul N.; Sweep, Fred C. G. J.; Dona, Margo; van Herwaarden, Antonius E.; Claahsen-van der Grinten, Hedi L. (Frontiers in Endocrinology, 2026)
The management of 21-hydroxylase deficiency (21OHD), the most common form of congenital adrenal hyperplasia, remains challenging as both over- and undertreatment with hormone replacement therapy are associated with short and long-term complications. Monitoring of treatment efficacy typically combines clinical assessment with biochemical evaluation by measuring specific steroids. Currently, androstenedione and 17-hydroxyprogesterone are the most commonly measured biomarkers, and their concentrations are interpreted using available reference intervals. However, inter-center variation in the concentrations of these steroids has been observed, likely due to the heterogeneity in monitoring practices and analytical methods. Additional sources of variation include the selection of biological matrix, timing of sample collection relative to diurnal rhythm and medication administration, and interpretative challenges of biomarker levels. Age-dependent fluctuations in steroid concentrations, particularly within the pediatric population, underscore the necessity for age-specific reference intervals. This review evaluates current monitoring strategies and reported reference intervals, and explores emerging biomarkers, including 11-oxygenated androgens and indicators of glucocorticoid receptor sensitivity, along with non-invasive sampling approaches. Together, these developments may enhance the precision and ease of disease monitoring in patients with 21OHD. Overall, this review emphasizes the need for standardized monitoring practices and method- and age-specific reference ranges, aiming for assay harmonization and optimal disease control.